Pemberdayaan Masyarakat dalam Melakukan Teknik Relaksasi Otot Progresif Pada Penderita Ostepororosis di Desa Bangun Rejo Kecamatan Tanjung Morawa Provinsi Sumatera Utara Tahun 2025 - Petra Diansari Zega; Ali Imran Sirait; Eko Murdianto; Sri Muliati Nendah; Nurcahaya Sihombing (Lembaga Pengembangan Kinerja Dosen, 2025)
Osteoporosis is a metabolic bone disorder characterized by a decrease in bone density and strength, making bones more fragile and susceptible to fractures. People with osteoporosis often complain of pain. One of the pain management methods for osteoporosis patients is progressive muscle relaxation. This community service activity empowers the public to practice progressive muscle relaxation techniques. The pre-test results showed that the majority of the community’s knowledge about osteoporosis and pain management was in the poor category, at 79.5%. After education and simulation of the progressive muscle relaxation technique were conducted, there was an increase in the community’s knowledge about osteoporosis and pain management, with 61.4% in the good category. The conclusion of this community service activity is that empowering the community to independently perform progressive muscle relaxation techniques is very beneficial in reducing pain in people with osteoporosis.